Gender differences in social networks and physical and mental health: are social relationships more health protective in women than in men? - Shin, Huiyoung; Park, Chaerim (Frontiers in Psychology, 2023)
Background Individuals’ relationships are characterized by multidimensional aspects and the unique make-up of different features is more or less supportive of physical and mental health. The current study derived social network types based on an extended set of indicators reflecting the structure, function, and quality of relationships, then examined their associations with diverse physical and mental health outcomes separately for men and women. Methods Using samples of 620 South Korean adults (Mage = 53.52), Latent Profile Analysis (LPA) was used to uncover distinct social network types, and multiple regression analyses were conducted to examine the link between network types and health outcomes. Results LPA analysis derived four network types: diversified, family-(un)supported, friend- based, and restricted. The prevalence and configuration of network types differed between men and women: the family-unsupported type was more prevalent in women than in men whereas the restricted type was more prevalent in men than in women. An individual’s network type membership was significantly associated with one’s physical and mental health and the positive effects of an optimal network type and the negative effects of a non-optimal network type on mental health were much greater for women than they were for men. Discussion The findings suggest that women benefit more from supportive networks but that they are also more vulnerable to a lack of supportive (or the presence of conflict-filled) relationships, and highlight that having diversified and greater quality relationships, and avoiding conflicts are critical for women to have enhanced health.